Penerapan Model Pembelajaran ECIRR Dengan Media LKPD Untuk Mereduksi Miskonsepsi Pada Materi Larutan Asam Basa Kelas XI SMA Negeri 4 Manado - Achmad, Nur Ain N.; Waworuntu, Freetje; Lombok, John Z. L. (General Chemistry Journal, 2025)
Misconceptions are a condition where students experience errors in understanding the concepts taught by experts. Students’ misconceptions can be obtained through the learning methods used. This research aims to reduce misconceptions of class XI students at SMA Negeri 4 Manado regarding acid-base solution material using the ECIRR learning model with the help of LKPD media. The type of research used is descriptive research. The sample in this research was all students of class XI IPA 3, totaling 32 people. In this research, the data collection instrument was a multiple choice test with 12 questions along with the reasons according to the acid-base solution material. Data analysis in this research uses validity and reliability tests. From the research results, it was concluded that the percentage of the misconception category was reduced from 28.125% to 8.85%, then the percentage of the understanding category increased from 23.185% to 83.85%, and the percentage of the don’t understand category experienced a reduction from 48.69% to 7.3%.